Developments of Anticoagulants and New Agents with Anti-Coagulant Effects in Deep Vein Thrombosis - Dang, Yi-Ping; Chen, Yun-Fei; Li, Yi-Qing; Zhao, Lei (Mini Reviews in Medicinal Chemistry, 2017)
Deep Vein Thrombosis (DVT) has been known as a common medical problem all over the world. Thrombus traveling in blood vessels may lead to pulmonary embolism (PE), associated with high rates of mortality. Anticoagulant therapy is the mainstay treatment of DVT. Common anticoagulants, Vitamin K antagonists (VKAs), unfractionated heparin (UFH) and Low-molecular-weight heparin (LMWH) have been used in clinical application over decades, but can increase the risk of hemorrhage. Thereby, several new oral anticoagulants (NOACs) have been developed, which includes direct thrombin inhibitors (DTI) and direct factor Xa inhibitors. To be contrast with VKAs and UFH, NOACs have many advantages such as rapid offset action, few drug/food interactions and no need for routine coagulation monitoring, etc. Many NOACs are still being evaluated in Phase III clinical trials such as Betrixaban and Darexaban (YM150). However, NOACs still have problems to be solved such as lack of antidotes and laboratory monitoring, high drug costs, etc. Besides, several agents have already shown the potential to be new anticoagulants. Factor Xa play an important role in thrombin generation and coagulation pathway. Thus, the new compounds directly targeting on factor Xa for prevention DVT are highly anticipated. DPC423, a new series of 6-substituted coumarin derivatives and Phenyltriazolinones as potent factor Xa inhibitors have been recently reported. Recent studies revealed that agents extracted from botanicals not only have anti-coagulant effects but also possess other pharmacological activities such as anti-inflammation to alleviate the post-thrombotic syndromes. All the evidence above suggests that many new compounds might have great potential to be more effective and safe oral anticoagulants.
Keywords: anticoagulation potential